2021
DOI: 10.1002/pits.22610
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating secondary traumatic stress in preservice educators: A pilot study on the role of trauma‐informed practice seminars

Abstract: In this study, explore secondary traumatic stress (STS) in preservice teachers (PSTs) and if trauma-informed practices (TIPs) have the potential to mitigate STS. We hypothesize that PST who have had consistent and extensive exposure to TIP will experience lower levels of STS in their student teaching or residency than students who have not had this exposure. Thirty-four PST participated in the study. Twenty-one were women, 12 men, and 1 identified as nonbinary. Their average age was 31 years. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
2
Order By: Relevance
“…Contrary to previous research (Castro Schepers & Young, 2022), school personnel’s confidence in their trauma-informed practice was not found to be a mitigating factor in the relationship between ACEs profiles and STS in school personnel. Of note, Castro Schepers and Young (2022) measured attendance in a trauma-informed practice seminar as a means of examining differences in STS in teachers whereas the present study uses self-reported perceptions of confidence in trauma-informed practice.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to previous research (Castro Schepers & Young, 2022), school personnel’s confidence in their trauma-informed practice was not found to be a mitigating factor in the relationship between ACEs profiles and STS in school personnel. Of note, Castro Schepers and Young (2022) measured attendance in a trauma-informed practice seminar as a means of examining differences in STS in teachers whereas the present study uses self-reported perceptions of confidence in trauma-informed practice.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous research (Castro Schepers & Young, 2022), school personnel’s confidence in their trauma-informed practice was not found to be a mitigating factor in the relationship between ACEs profiles and STS in school personnel. Of note, Castro Schepers and Young (2022) measured attendance in a trauma-informed practice seminar as a means of examining differences in STS in teachers whereas the present study uses self-reported perceptions of confidence in trauma-informed practice. Results could be due to the fact that many trauma-informed school programs and training—along with our trauma-informed practice efficacy variable—focus on practices geared toward supporting students rather than those that look to help school personnel with their needs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Engaging pre- and in-service educators on training related to trauma-informed practices as well as self-care practices to mitigate the effects of compassion fatigue, secondary traumatic stress, and burnout is needed (Koenig et al, 2018 ; Miller & Flint-Stipp, 2019 ). For instance, a recent study indicated there is a relationship between training in trauma-informed practices and a reduction in rates of secondary traumatic stress for pre-service educators (Castro Schepers & Young, 2022 ). Training should not be limited to teachers—administrators, school-based mental health professionals, and support staff all benefit from training (Kataoka et al, 2018 ).…”
Section: Overview Of Student Traumamentioning
confidence: 99%